2020
DOI: 10.3389/fbioe.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chiral Discrimination of D-Phenylalanine Amino Acid Based on a Perylene Bisimide Derivative

Abstract: The interaction between homochiral substituted perylene bisimide (PBI) molecule and the D enantiomer of phenylalanine amino acid was monitored. Spectroscopic transitions of PBI derivative in aqueous solution in the visible range were used to evaluate the presence of D-phenylalanine. UV-visible, fluorescence, FT-IR, and AFM characterizations showed that D-phenylalanine induces significant variations in the chiral perylene derivative aggregation state and the mechanism is enantioselective as a consequence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…To this end, chiral polymers, foldamers, or biomolecules such as DNA or peptides have been employed to organize achiral chromophores through covalent or noncovalent interactions such as H-bonding, hydrophobic, or host–guest binding, , and have been shown to be effective in inducing chirality from one molecule to another. Other studies showed that chiroptical properties could appear upon chiral aggregation of molecules devoid of optical activity in solution. Tsunega et al have recently reported the use of cationic polymer–anionic chiral counterion assemblies as templates to prepare silica architectures that can induce chiroptical signals to adsorbed dyes and nanocrystals. , Silica with chiral molecular prints has also been used for enantioselective separation/recognition and has been shown to have the ability to induce chiral arrangement to the achiral molecules adsorbed on its surface . Our previous work has shown that it is possible to induce chiroptical properties to gold nanoparticles or metal complexes organized on the surface of silica nanohelices , or using biphenyl-linked polysilesquioxane through a sol–gel transcription of self-assembled nanohelices from dicationic gemini surfactants.…”
Section: Introductionmentioning
confidence: 98%
“…To this end, chiral polymers, foldamers, or biomolecules such as DNA or peptides have been employed to organize achiral chromophores through covalent or noncovalent interactions such as H-bonding, hydrophobic, or host–guest binding, , and have been shown to be effective in inducing chirality from one molecule to another. Other studies showed that chiroptical properties could appear upon chiral aggregation of molecules devoid of optical activity in solution. Tsunega et al have recently reported the use of cationic polymer–anionic chiral counterion assemblies as templates to prepare silica architectures that can induce chiroptical signals to adsorbed dyes and nanocrystals. , Silica with chiral molecular prints has also been used for enantioselective separation/recognition and has been shown to have the ability to induce chiral arrangement to the achiral molecules adsorbed on its surface . Our previous work has shown that it is possible to induce chiroptical properties to gold nanoparticles or metal complexes organized on the surface of silica nanohelices , or using biphenyl-linked polysilesquioxane through a sol–gel transcription of self-assembled nanohelices from dicationic gemini surfactants.…”
Section: Introductionmentioning
confidence: 98%
“…[40] PBI results mainly organized in H aggregates within the thin film, since the A 540 /A 508 value is below 0.9 (black line in Figure 4a). [41] The presence of metallic nanostructures influences the aggregation state of PBI with an inversion of intensity of such bands (purple line in Figure 4a) suggesting a slight change in the aggregates/monomers equilibrium in favor of the monomeric forms.…”
Section: Pbi/auns Deposition Procedures and Thin Films Characterizationmentioning
confidence: 99%
“…Among these antibiotics, amoxicillin, cephalexin and ampicillin are included in the World Health Organization's list of essential medicines. D-Phenylalanine is used in the preparation of nateglinide, a drug for the treatment of type 2 diabetes (Bettini et al, 2020). D-valine is used in the synthesis of tau-fluvalinate, a pyrethroid pesticide (Chen et al, 2016).…”
Section: Biomedical and Biotechnological Applications Of Ncaasmentioning
confidence: 99%